GOVERNMENTAL SYMBOLS AND OUTSTANDING DATES OF GREAT BRITAIN (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article explores the most significant governmental symbols and historical milestones of Great Britain, shedding light on the cultural, political, and historical elements that shape its national identity. Through a detailed overview of symbols such as the Royal Coat of Arms, the Union Jack, and iconic government buildings, the paper emphasizes how these emblems reflect the monarchy and democratic values. Furthermore, the article highlights key historical dates that have influenced the political landscape of the country, from the Magna Carta to Brexit, offering insights into the evolution of British governance and tradition. This work aims to provide readers with a deeper understanding of how history and symbolism are intertwined in defining the British state.